(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
The practical application of gamification in English as a Foreign Language (EFL) teaching is an evolving area of interest in contemporary pedagogy.This paper investigates how game-based learning can improve student engagement and language acquisition. By integrating methodological approaches such as task-based learning, collaborative learning, and digital tools, educators can create an engaging and effective EFL classroom. This study utilizes both qualitative and quantitative methodsto explore the impact of gamification on students’ speaking, listening, and vocabulary skills. The results show that students who engaged with gamified activities demonstrated higher motivation and improved performance compared to those who followed traditional pedagogical approaches.